Pengaruh Perilaku Keuangan Hijau dan Akses terhadap Pembiayaan Berkelanjutan terhadap Pengembangan UMKM Fashion di Medan: Pengaruh Perilaku Keuangan Hijau dan Akses terhadap Pembiayaan Berkelanjutan terhadap Pengembangan UMKM Fashion di Medan - Khairatun Nazah (CV. AFDIFAL MAJU BERKAH, 2026)
This study examines the influence of green financial behavior and access to sustainable financing on the development of fashion MSMEs in Medan. The growing importance of sustainability in business practices has encouraged MSME actors to adopt more responsible financial decisions and seek financing schemes that support long-term business growth. This study employed a quantitative approach with an associative causal design. The population consisted of 207 fashion MSME actors in Medan, and 150 respondents were selected using purposive sampling based on specific criteria, namely operating in the fashion sector, having been active for at least one year, and being willing to provide information related to financial behavior, financing access, and business development. Data were collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that green financial behavior has a positive and significant effect on fashion MSME development, with a path coefficient of 0.402, a t-statistic of 5.214, and a p-value of 0.000. Access to sustainable financing also has a positive and significant effect on fashion MSME development, with a path coefficient of 0.376, a t-statistic of 4.687, and a p-value of 0.000. The R-square value of 0.614 indicates that green financial behavior and access to sustainable financing explain 61.4% of the variation in fashion MSME development, while the Q-square value of 0.421 confirms that the model has good predictive relevance. These findings suggest that the development of fashion MSMEs in Medan is shaped not only by creativity and market opportunities, but also by the ability of business actors to integrate sustainability principles into financial management and financing decisions. The study provides practical implications for MSME actors, financial institutions, and local governments in strengthening sustainable and competitive fashion-based entrepreneurship.